Thirst in critical patients and its associated factors - Laura Vicentim Berbert; Isadora Pierotti; Leonel Alves do Nascimento; Isabela Bossi Faleiros; Meiriane Pizani Scobare de Oliveira; Rafael Alexandre Biz; Rafaela Vieira Jorge; Lígia Fahl Fonseca (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to assess prevalence, intensity, discomfort, defining characteristics of thirst and signs of oral mucosa hydration in Intensive Care Unit patients. Methods: quantitative and analytical study, carried out in a tertiary hospital in six of the seven Intensive Care Units, with a sample of 60 patients. Variables related to thirst were analyzed according to their nature. Results: prevalence of thirst was 76.7%, with a mean intensity of 7.2. The main Objective Oral Mucosa Scale score was 2 (61.7%), corresponding to dry lips and moist mouth. Prevalent defining characteristics were thick saliva (80%), constant swallowing of saliva (76.7%), desire to drink water (75%), dry lips (73.3%) and dry throat (70%). Positive correlations were identified between scales and thirst intensity, water restriction and hospitalization duration. Conclusions: the statistically significant correlations reflect the complexity and multifactorial nature of thirst, demonstrating the need to use identification and measurement instruments in the critical population.